2009
DOI: 10.1002/jsfa.3467
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minolta colorimeter and machine vision system in measuring colour of irradiated Atlantic salmon

Abstract: BACKGROUND: Minolta and machine vision are two different instrumental techniques used for measuring the colour of muscle food products. Between these two techniques, machine vision has many advantages, such as its ability to determine L * , a * , b * values for each pixel of a sample's image and to analyse the entire surface of a food regardless of surface uniformity and colour variation. The objective of this study was to measure the colour of irradiated Atlantic salmon fillets using a hand-held Minolta color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 16 publications
4
40
0
1
Order By: Relevance
“…The colors of broiler breast meats, determined using imaging analysis, had higher L* and b* values, but a lower a* value, compared with those obtained using direct measurement. Previous studies have found that the L* and b* values of salmon (Yagiz et al, 2009), chicken, and pork (Girolami et al, 2013), measured using a machine vision system, demonstrated higher values compared with those obtained using a colorimeter. The color of the surface of the meat could be affected by the amount of overall light scattering and reflected electromagnetic wavelength, which was related to the amount of applied light that penetrates into the meat sample (Girolami et al, 2013).…”
Section: Colors Of Breast Meat Determined By Direct Measurement and Imentioning
confidence: 81%
“…The colors of broiler breast meats, determined using imaging analysis, had higher L* and b* values, but a lower a* value, compared with those obtained using direct measurement. Previous studies have found that the L* and b* values of salmon (Yagiz et al, 2009), chicken, and pork (Girolami et al, 2013), measured using a machine vision system, demonstrated higher values compared with those obtained using a colorimeter. The color of the surface of the meat could be affected by the amount of overall light scattering and reflected electromagnetic wavelength, which was related to the amount of applied light that penetrates into the meat sample (Girolami et al, 2013).…”
Section: Colors Of Breast Meat Determined By Direct Measurement and Imentioning
confidence: 81%
“…The pictures acquired were resized, cleaned and converted to bmp files using Adobe Photoshop 13.0.1.3 CS 6 (Adobe Systems Inc, California, U.S.A.) before they were analyzed using LensEye Version 11.4.1 software (ECS, Gainesville, FL, USA). LensEye provided the average L*, a* and b* values of the samples (Yagiz et al, 2009). …”
Section: Computer Based Image Analysismentioning
confidence: 99%
“…Furthermore, if there is a high-fat ratio in fillets, the uneven colour distribution increases after smoking (Espe et al, 2002). Therefore, it is not possible to determine the true colour of seafood by using conventional instrumental colour analysis methods (Kong, et al, 2015b;Yagiz et al, 2009). Computer-based image analysis (CBI) could be an alternative at this point.…”
Section: Introductionmentioning
confidence: 99%
“…MVS also provides the colour spectrum and other visual attributes of the sample [24,25]. The performance of a hand-held Minolta colorimeter and a MVS in measuring the colour of Atlantic salmon (S. salar) fillets treated with different electron beam doses (0, 1, 1.5, 2, and 3 kGy) was compared [26]. The average L * , a * , and b * values measured by MVS resulted in orange colours very close to that of the original sample ( Fig.…”
Section: Visual Quality Determination Based On Colourmentioning
confidence: 99%